Efektivitas Peran Komisi Perlindungan Anak Indonesia dalam menangani Kasus Bullying Terhadap Anak - Ariani, Anisa Dewi; Prawitasari, Nining Yurista (Innovative: Journal Of Social Science Research, 2024)
Bullying cases are prone to occur among children and are one of the cases that often occur in Indonesia. The large number of cases of bullying among children will have a negative impact on children's physical, mental and emotional development. The Indonesian Child Protection Commission is often in the public spotlight because of the increase in the number of bullying cases every year. This research aims to investigate the effectiveness of the role of the Indonesian Child Protection Commission in handling cases of bullying against children. The research method used is empirical legal research with data collected through interviews with members of the Indonesian Child Protection Commission, tabulation of data on bullying cases and also literature studies which include books, journals, laws and regulations and trusted websites. The research results show that the role of the Indonesian Child Protection Commission in handling bullying cases is considered effective, because the number of bullying cases has decreased based on data that has been recapitulated from 2021 to 2023.